Efektivitas Pengendalian Internal atas Transaksi Kas - Rosy Aprieza Puspita Zandra; Zumrotus Sholihah (Jurnal Kajian Akuntansi, 2018)
Banking activities need an assessment of the level of profitability is conducive so that the business to be achieved can be maximized. To maximize the rate of return of such profits, the control and supervision of stricter controls of cash control that occur in the operation. This study intends to observe, and understand the description of the internal control system of cash transactions that occur within the object of research environment. The object chosen in this study is the Sharia Rural Bank (BPRS) Bhakti Sumekar Sumenep. Descriptive research is used in this research, with informants taken based on purposive sampling technique. Based on the results of research, it is known that the internal cash control is quite effective that can be seen from the level of compliance and vigilance of the bank in maintaining its wealth. However, the actual implementation that has occurred is still not in accordance with the standart operating procedure that has been used.